Multiple Grade IV Pressure Injuries in a Young Boy: ALook Into the Pathognomic and Management of Iliac Crest Pressure Injury - Shah, Sheerin; Mittal, Rajinder K; Garg, Ramneesh; Singh, Karan; Gautam, Sumit (Indian Journal of Case Reports, 2022)
Pressure Injury (PI), not only exerts physical burden on a patient’s body but also adds to his mental and economic stress [1]. Chronically ill, bed ridden and aged patients are always predisposed to development of pressure injury unless nursed with frequent position changes over an air mattress [2]. Every now and then, we come across, young patients who develop PI, either because of insensate and powerless lower limbs or prolonged bed ridden medical conditions. The temptation to close any pressure ulcer primarily should always be resisted [3]. We hereby, present a case report of a 17 years boy, who sustained cervical spine injury after road traffic accident, 10 months back and later developed multiple pressure injuries over bilateral trochanter and left ilium. We discuss the pathognomics of occurrence of pressure injury at unusual sites like ilium and our management for coverage of such defects.